Implementation of Diabetes Self Management Education (DSME) Towards Reducing Blood Glucose Levels in Patients With Type II Diabetes Mellitus in the Wijaya 4 Room of X - Laikha Meyda Sari; Shindi Hapsari (Sean Institute, 2026)
Diabetes mellitus type II is a chronic metabolic disease characterized by elevated blood glucose levels and requires effective self-management to prevent complications. This study aimed to describe the effect of Diabetes Self-Management Education (DSME) on reducing blood glucose levels in patients with type II diabetes mellitus in the Wijaya Kusuma 4 Ward of RSUD Dr. Adhyatma, MPH, Central Java Province. A descriptive case study design was used involving two patients with type II diabetes mellitus. Data were collected through interviews, observations, blood glucose measurements, and the Diabetes Knowledge Questionnaire (DKQ-24). DSME was implemented in four structured sessions over three days. The results showed a decrease in blood glucose levels in both patients and an improvement in knowledge after the intervention. These findings indicate that DSME is effective as a non-pharmacological nursing intervention to reduce blood glucose levels in patients with type II diabetes mellitus